2021
DOI: 10.1186/s12891-021-04403-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for bone loss in rheumatoid arthritis patients from South China: modeled by three methods

Abstract: Background To explore the prevalence of bone loss among patients with rheumatoid arthritis (RA) and healthy controls (HC) and further explored the risk factors for osteopenia and osteoporosis of RA patients. Methods A cross-sectional survey was undertaken in four hospitals in different districts in South China to reveal the prevalence of bone loss in patients. Case records, laboratory tests, and bone mineral density (BMD) results of patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Second, the results merely reflected the population with normal BMD values, with pregnant women excluded due to the specialty of DXA examination. None of these candidates’ BMD value from the NHANES was lower than −1, which was considered to be bone loss according to the the diagnosed criteria of the WHO [ 43 ]. It would be better if a control group could be set up.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the results merely reflected the population with normal BMD values, with pregnant women excluded due to the specialty of DXA examination. None of these candidates’ BMD value from the NHANES was lower than −1, which was considered to be bone loss according to the the diagnosed criteria of the WHO [ 43 ]. It would be better if a control group could be set up.…”
Section: Discussionmentioning
confidence: 99%
“…In women with RA and an age >50 years, vitamin D deficiency was significantly associated with new clinical and new osteoporotic fractures [ 69 ]. Hu et al, assessed risk factors for osteoporosis in 405 patients with RA and concluded that high serum levels of vitamin D protected against bone loss whereas advanced age, low BMI, and increased serum uric acid levels were associated with osteoporosis [ 70 ]. Overall, this part can be summarized such that the following general risk factors of osteoporosis are also effective in RA: post-menopause, advanced age, low body mass index, sarcopenia, vitamin D deficiency, and high cumulative doses of glucocorticoids.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is one of the most common autoimmune diseases that in the early stages of the disease begins with pain and symmetrical swelling of the small joints of the hands, feet, swelling of the soft tissue around the joint and morning stiffness and fatigue 1 4 and it is characterized by persistent synovitis and progressive destruction of symmetrical multi-joints and intra-articular manifestations including subchondral lesions, decreased bone mass, and reduced generalized bone density 4 7 . The prevalence of RA in the general population is about 1%, but is more common in the 50 s and 60 s and is higher in women than men 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%